MANAJEMEN KEPENGASUHAN SANTRI DI PONDOK PESANTREN MBS MAS MANSYUR NGAWI: TANTANGAN DAN SOLUSINYA - Budi, Sunaryanto; Gesang Saputra, Alan Lutfi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2024)
This research aims to analyze the management of student care at the MBS Mas Mansyur Ngawi Islamic Boarding School, with a focus on the challenges faced and solutions that can be implemented. The research method used is descriptive qualitative with a case study approach. Data was collected through in-depth interviews, participant observation and documentation studies. The research results show that the main challenges in managing student care include limited human resources, differences in student backgrounds, and the dynamics of technological development. The proposed solutions include improving the quality of caregivers, developing character development programs, and integrating technology in the Islamic boarding school management system. Nurturing students is a crucial aspect in shaping the character and behavior of students during their education. The main challenges faced in parenting include discipline, effective communication between caregivers and students, as well as consistent application of Islamic values ​​in everyday life. Apart from that, limited human resources and facilities are also obstacles in achieving parenting effectiveness. This article offers solutions in the form of optimizing parenting programs based on psychological and spiritual approaches, increasing the capacity of caregivers through training, and improving communication systems between caregivers, students and parents. It is hoped that the results of this research can be a reference for Islamic boarding school managers in improving parenting management, so that they are able to produce student graduates who have noble character and good social skills.